The added value of rail freight transport in Belgium. (September 2022) - Troch, Frank; Meersman, Hilde; Sys, Christa; Van De Voorde, Eddy; Vanelslander, Thierry
Abstract: Rail freight transport is facing contradicting realities. Ambitious goals to stimulate this mode of land transport at the expense of the less sustainable and over congested road transport, are going hand in hand with a continuous decrease in usage and modal share statistics. As it is known that a lack of flexibility is holding back the development of this mode, this research wants to evaluate what could be the direct economic impact of rail freight transport in Belgium if these bottlenecks are resolved. By generating three economic indicators, evaluating the added value per unit of workforce, the added value per unit of production and the added value range for the incumbent rail freight operator, the productivity and efficiency of rail freight transport services in Belgium are evaluated and compared with the four main competitors. Results show that for all indicators a positive direct economic impact and an upward trend can be observed, although data collection proves to be challenging and historical data is inexistent or inconsistent due to the absence of joint cost allocation, which is clearly a point of attention for policymakers. Results also indicate that liberalization of the rail freight market is stimulating rail freight operators to improve their efficiency by rethinking their business. Graphical abstract: Image 1